Perceived Effectiveness and Sustainability of Face Masks Among German Citizens During the 2nd Wave of the COVID-19 Pandemic—A Cross-Sectional Study - Maren Theresa Christin Fendt; Walter Leal Filho; Jelena Barbir; Juliane Boenecke (Frontiers in Public Health)
BackgroundThe COVID-19 pandemic, which began at the end of 2019, has led to a significant increase in the demand for face masks in Germany and around the globe. Since non-reusable masks are often not correctly disposed of and are not biodegradable, their increasing use harms the environment. Both the ongoing pandemic and the rising environmental pollution eventually pose a threat to human health. Yet, it is unclear whether mask users are conscious of this, and which factors influence their choice of face masks. This study investigates the user preferences, perceived effectiveness, and the sustainability of different mouth/nose protection (MNP) to lay the foundation for developing more sustainable and effective alternatives.MethodsA national (Germany-wide) cross-sectional study with a sample of 1,036 participants was conducted. Descriptive data analysis was deployed to describe trends and socio-demographic differences among the respondents. Different socio-demographic groups among the respondents were compared regarding their infection risk perception, compliance toward the use of personal protective measures, their choice of MNP, and knowledge level of sustainability and effectiveness of various MNP using inferential statistics (Chi2 test/Whitney–Mann-U-test/Kruskal–Wallis-test).ResultsThe results suggest that, in addition to protective effectiveness, the reusability of MNP is important to not just most respondents but especially to older participants. In contrast, the price, shape, and design were not as important. The knowledge level of the effectiveness and sustainability of MNP was high among the participants and was not associated with socioeconomic characteristics. However, the knowledge level directly influenced the choice of MNP.ConclusionThere seems to be an inclination to use sustainable MNP, provided their level of protection is similar to medical masks or FFP2/FFP3 masks. The willingness to wear a sustainable option increases with age.